IMPLEMENTASI PENGELOLAAN DANA DESA STUDI KASUS PADA DESA LAMA BARU KECAMATAN SEI LEPAN KABUPATEN LANGKAT - .HERTI DIANA HUTAPEA (JURNAL ILMIAH MAKSITEK, 2018)
The purpose of this study was to determine the implementation of village fund management based on Permendagri No. 113 of 2014 in the Lama Baru Village, Sei Lepan Subdistrict, Langkat Regency, in 2016 is in accordance with Permendagri No. 113 of 2014.This type of research is descriptive research with a qualitative approach by describing a particular phenomenon or condition as a research method. The data collection technique used was in-depth interviews (semi-structured in-depth interviews, passive participatory observation and documentation). And data analysis techniques are carried out by stages of data collection, data reduction, data validity testing, after data reduction, then the data is tested for validity with credibility. Data testing was carried out using triangulation techniques, data presentation in the form of village financial management analysis, suitability analysis of documents related to village financial management in the Baru New Village with village financial management according to Permendagri No 113 of 2014 and Conclusions.The conclusion shows that the Financial Management of Lama Baru Village, Sei Lepan Subdistrict, Langkat Regency shows that the overall activities of financial management are in accordance with the Minister of Home Affairs Regulation No.113 of 2014. Starting from the planning stage, which starts with the implementation of musrembangdes as a forum to determine the activities that will be carried out and prioritized which will produce a budget plan to implement the work budget that will be allocated to work activities in the Lama Baru Village, Sei Lepan Subdistrict, Langkat Regency, in the training phase in which all transactions that occur in village financial management have been recorded systematically and chronologically. However, the New Lama Village Government in conducting transactions related to village finances still does not use bank transfer services to third parties because the Lama Baru Village Government uses the self-management system in its financial management, namely using the labor services in the Lama Baru Village. In the accountability stage, it is still not carried out in accordance with Permendagri No. 113 of 2014, namely the exclusion of the Government Report of the Government and Regional Governments that entered the village in the accountability report on the realization of the APBDesa 2016 Fiscal Year as well as the lack of public awareness of the implementation of the APBDesa implemented by the village apparatus.It is expected that the Lama Baru Village Government of Sei Lepan District can improve or improve the financial management of the Lama Baru Village in Sei Lepan Subdistrict, Langkat Regency in the future in terms of conducting transactions both receipts and expenditures of village finance using bank transfer services to third parties and the New Lama Village District Government. Sei Lepan Langkat Regency should make a report on the program of the Government and Regional Government that enters the village and includes it in the accountability report on the realization of the APBDesa implementation of Fiscal Year 2016.